Index (Zbornik radova međunarodnog teološkog skupa KBF-a u Splitu, 2018)
Religious experience and aesthetic experience have always more or less successfully permeated. There is no religion in the history of mankind that has not expressed its experiences also through artistic searching for beauty. Beauty, in fact, has always been seen as one of the privileged links between man and the divine. Therefore, the fundamental moments of all religions, such as the sacred texts, prayer and ritual practices, traditions, architecture, doctrines and theology, are open to the aesthetic dimension too.